Deep soil desiccation hinders nitrate leaching to groundwater in the global largest apple cultivation area - Ge, Dong; Gao, Xiaodong; Jiang, Pengyan; Li, Bin; He, Nana; Wu, Yabiao; He, Qinghai; Cai, Yaohui; Li, Changjian; Zhao, Xining (Journal of hydrology (Amsterdam), 2024)
•Residual nitrate was mainly accumulated in the 4.0–8.8 m in apple orchards of CLP.•Nitrate accumulation varied with mean annual precipitation and stand age.•Mean annual precipitation (MAP) and N fertilizer application amounts dominated nitrate accumulation in the soil.•Deep soil desiccation hinders residual nitrate leaching to groundwater. Massive use of N fertilizer in apple orchards aids China’s Loess Plateau (CLP) to become the largest region of apple production in the world, but it also leads to substantial nitrate accumulation in the vadose zone, posing a potential environmental risk. However, a holistic understanding of the spatial patterns and controls of soil nitrate in the vadose zone of apple orchards remains understudied, which is unfavorable for the formulation of a science-based N application strategy. To this end, we collected a total of 2852 paired data across apple orchards on the CLP from 52 published literature and 1000 paired data from our field sampling. We found that residual nitrate accumulation primarily occurred in the top 4–8.8 m soil layer, and it varied according to mean annual precipitation (MAP) and stand age; the accumulation peaked in sites with MAP of 500–600 mm and declined with a decrease in MAP; and among various stand ages, the highest nitrate content was observed in the 25-yr-old orchard. It was found that MAP and N fertilizer application amounts dominated nitrate accumulation in the soil. Furthermore, the desiccation index of the soil layer below the maximum cumulative depth was identified as the main factor influencing soil nitrate maximum accumulation depth . This means that deep soil desiccation hinders nitrate leaching towards deeper layers and reduces the risk of groundwater contamination. The findings here may provide insights into sustainable nitrogen and water management in apple orchards on the CLP and potentially in other similar regions.